Straightforward synthesis of aliphatic polydithiocarbonates from commercially available starting materials. Issue 42 (11th October 2022) - Sehn, Timo; Huber, Birgit; Fanelli, Julian; Mutlu, Hatice
Abstract : Herein, a novel 1, 1′-carbonyldiimidazole (CDI ) mediated polymerization methodology that complements ring-opening polymerization (ROP) and unlocks a greater synthetic window to less-recognized polydithiocarbonates is presented. Abstract : Herein, a novel 1, 1′-carbonyldiimidazole (CDI ) mediated polymerization methodology that complements ROP and unlocks a greater synthetic window to less-recognized polydithiocarbonates is presented.